2014
DOI: 10.18632/oncotarget.2377
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 promotes the proliferation and tumor formation of cervical cancer cells through the Wnt/β-catenin signaling pathway

Abstract: Leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5), a seven transmembrane receptor known as a potential stem cell marker for intestinal crypts and hair follicles, has recently been found to be overexpressed in some types of human cancers. However, the role of LGR5 in cervical cancer remains unclear. In this study, the expression of LGR5 gradually increases from normal cervix to cervical cancer in situ and to cervical cancers as revealed by immunohistochemistry and western blot analyses. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 41 publications
7
51
0
Order By: Relevance
“…The mechanism of sensitization by Lgr5 needs further investigation. Most likely Lgr5 makes cells more vulnerable to chemotherapy by increasing their propensity to divide through activation of the Wnt/β-catenin pathway [18]. In our experiments, Lgr5 promotes cell adhesion, which was shown earlier with another CRC cell line [19].…”
Section: Discussionsupporting
confidence: 76%
“…The mechanism of sensitization by Lgr5 needs further investigation. Most likely Lgr5 makes cells more vulnerable to chemotherapy by increasing their propensity to divide through activation of the Wnt/β-catenin pathway [18]. In our experiments, Lgr5 promotes cell adhesion, which was shown earlier with another CRC cell line [19].…”
Section: Discussionsupporting
confidence: 76%
“…Of all these CSC markers, Lgr5 and CD44 are well known targets of the Wnt signaling pathway and have been implicated in cancer invasion and metastasis through their involvement in tumor formation and proliferation [85][86][87]. Lgr5 induces the Wnt/ -catenin pathway enhancing tumor formation and cancer cell proliferation [85]. The gradual increase in expression of Lgr5 we observed in our study was similar to that observed for cervical cancer [85].…”
Section: Cd133 Is a Known Cancer Stem Cell Marker In Cancers Such As supporting
confidence: 85%
“…and for is its role in metastasis in these cancers [84]. Of all these CSC markers, Lgr5 and CD44 are well known targets of the Wnt signaling pathway and have been implicated in cancer invasion and metastasis through their involvement in tumor formation and proliferation [85][86][87]. Lgr5 induces the Wnt/ -catenin pathway enhancing tumor formation and cancer cell proliferation [85].…”
Section: Cd133 Is a Known Cancer Stem Cell Marker In Cancers Such As mentioning
confidence: 99%
“…In ovarian, breast and lung cancer cells, high expression of LGR5 has been correlated with advanced stages, poor overall survival and metastasis [103][104][105][106]. In cervical cancer, LGR5 promotes proliferation and tumor formation through Wnt/β-catenin signaling [107].…”
Section: Prognostic Value Of Lgrsmentioning
confidence: 99%